PENGARUH KOMPETENSI DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA GURU PADA SMP NEGERI H WUKIRSARI KECAMATAN TUGUMULYO KABUPATEN MUSI RAWAS - Surajiyo Surajiyo (Jurnal Media Ekonomi (JURMEK), 2017)
Effect of Competence and Organizational Commitment on Teacher Performance at H Wukirsari State Middle School, Tugumulyo District, Musi Rawas Regency. The purpose of this study was to determine the effect of competency and organizational commitment partially and simultaneously on teacher performance in the H Wukirsari State Middle School, Tugumulyo District, Musi Rawas Regency. The population and sample in this study were 37 teachers. The results of the regression equation obtained are: Y = 9.635 + 0.326 X1 + 0.399 X2 .. The coefficient of determination (R2) obtained at 0.621 or 62.1% and the remaining 37.9% is influenced by other variables not examined in this research. The conclusion is that: Competence has an influence on Teacher Performance in H Wukirsari State Middle School, Tugumulyo Subdistrict, Musi Rawas Regency, with a tcount = 4.894 greater than t table = 1.688, with a significant level = 0,000. Organizational commitment has an influence on Teacher Performance at H Wukirsari State Middle School, Tugumulyo Subdistrict, Musi Rawas District, with a tcount = 6.090 greater than t table = 1.688, with a significant level = 0,000. Competence and Organizational Commitment have an influence on Teacher's Performance at H Wukirsari State Middle School, Tugumulyo Subdistrict, Musi Rawas Regency, with Fcount = 27.851 greater than Ftable = 3.28, with a significant level of 0.000.